2022
DOI: 10.1126/sciadv.add2696
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a chordate-specific mechanism for myoblast fusion

Abstract: Vertebrate myoblast fusion allows for multinucleated muscle fibers to compound the size and strength of mononucleated cells, but the evolution of this important process is unknown. We investigated the evolutionary origins and function of membrane-coalescing agents Myomaker and Myomixer in various groups of chordates. Here, we report that Myomaker likely arose through gene duplication in the last common ancestor of tunicates and vertebrates, while Myomixer appears… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Myoblasts are undifferentiated cells implicated in the repair of muscle injury and skeletal muscle development during embryonic growth (Zhang et al, 2022). During myoblasts differentiation, the ER is prone to dysregulation of homeostasis, inducing ER stress and culminating in the unfolded protein response (UPR), an evolutionarily conserved mechanism of cell survival (Nakanishi et al, 2007).…”
Section: Biological Functionsmentioning
confidence: 99%
“…Myoblasts are undifferentiated cells implicated in the repair of muscle injury and skeletal muscle development during embryonic growth (Zhang et al, 2022). During myoblasts differentiation, the ER is prone to dysregulation of homeostasis, inducing ER stress and culminating in the unfolded protein response (UPR), an evolutionarily conserved mechanism of cell survival (Nakanishi et al, 2007).…”
Section: Biological Functionsmentioning
confidence: 99%
“…Although we have used ASEC-1 to explore Hh signaling here, this cell line can be used to broadly explore gene function in anoles. We note that Zhang and colleagues were able to isolate a subclone of ASEC-1 that can be induced to initiate myogenesis in culture (Zhang et al, 2022). They subsequently used this subclone to investigate the function of the mymk gene in lizard myoblasts.…”
Section: Understanding the Role Of Primary Cilia In Reptile Hh Signal...mentioning
confidence: 99%
“…A recent study has suggested that MYMK and MYMX have coevolved in the vertebrates [119]. These observations indicate that MYMK and MYMX evolved together for myoblast fusion, parallel to the emergence of sarcomeric muscle and EC coupling in this lineage [120].…”
Section: Divergent Fusion Machinery Between Amniotes and Anamniotesmentioning
confidence: 99%